A study on the outbreak of dengue fever in a tertiary care children’s hospital in southern Tamil Nadu, India - Premkumar, Belgin; S., Baburaj; N., Margaret Hepzibah; P., Misha K.; Abraham, Binu (International Journal of Contemporary Pediatrics, 2019)
Background: Dengue fever is the most rapidly spreading mosquito-borne viral disease in the world.Incidence has increased 230-fold with increasing geographic expansion with potential for further spread. The rapidly expanding global footprint of dengue is a public health challenge with an economic burden. This study’s objective is to assess the outbreak of epidemic of dengue fever in a tertiary care children hospital and to describe their socio-demographic, clinical outcome and serological profile. Methods: It is an observational descriptive study conducted for a period of 1 year in less than 12 years old children in a tertiary care hospital at Southern Tamil Nadu. Results: Among the 360 children admitted with dengue fever, there were 198 boys (55%) and 162 (45%) were girls. Maximum incidence of dengue incidence was seen in infants less than 1 year (25%). The highest number of cases were admitted during September and October. The most common affected age group was less than 3 years with 179 (49%). Among the cases, 297 (82%) were of severe dengue which constitute dengue haemorrhagic fever-183(38%) and Dengue shock syndrome 114 (62%). Serological analysis showed NS1 Ag was positive in 144 children (40%), Dengue IgM was positive in 54 children (15%), both IgM and IgG positive in 126 children (35%) and IgG was positive in 36 children (10%). Out of the total children admitted with dengue fever, the case fatality was 0.5% (2 children). Conclusions: This study highlights the importance of WHO clinical criteria for early diagnosis of severe dengue. Moreover, the early and intensive management reduces the mortality significantly.